2021
DOI: 10.2147/ccid.s291170
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Value of Serum Ferritin for Telogen Effluvium: A Cross-Sectional Comparative Study

Abstract: This study aimed to explore the relationship between serum ferritin levels and telogen effluvium. Patients and Methods: A total of 193 telogen effluvium patients and 104 female androgenetic alopecia patients were included. We collected the test result of serum ferritin levels, compared with the results of 183 healthy subjects. Receiver Operator Characteristic curves were generated to assess the potential diagnostic value of serum ferritin in telogen effluvium patients. Results: The serum ferritin in telogen ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Hence these cutoff levels should be based on loco‐regional studies instead of extrapolating findings of studies from countries with different diets. Another theory suggests that an upregulation of hepcidin leads to lower iron being available for the hair follicle in order to compensate for the essential iron requirements 28,29 . Paradoxically, some studies have found that low serum ferritin levels are seen in female androgenetic alopecia, but not in telogen effluvium 30 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence these cutoff levels should be based on loco‐regional studies instead of extrapolating findings of studies from countries with different diets. Another theory suggests that an upregulation of hepcidin leads to lower iron being available for the hair follicle in order to compensate for the essential iron requirements 28,29 . Paradoxically, some studies have found that low serum ferritin levels are seen in female androgenetic alopecia, but not in telogen effluvium 30 .…”
Section: Methodsmentioning
confidence: 99%
“…Another theory suggests that an upregulation of hepcidin leads to lower iron being available for the hair follicle in order to compensate for the essential iron requirements. 28,29 Paradoxically, some studies have found that low serum ferritin levels are seen in female androgenetic alopecia, but not in telogen effluvium. 30 Hence, more data are needed to ascribe a definitive association of ID with alopecia.…”
Section: Ironmentioning
confidence: 99%
“…1,3,44 Androgenetic alopecia AGA, often called male pattern baldness, is an autosomal dominant disorder that gradually transforms terminal hairs into intermediate and vellus hairs. [45][46][47] It is the most common progressive baldness in both men and women; however, clinical symptoms differ between genders. In men, AGA causes gradual thinning and vertex loss; in women, hair loss affects the frontal scalp and vertex, while the frontal hairline is spared, resulting in a more visible scalp.…”
Section: Non-scarring Alopeciamentioning
confidence: 99%
“…7 Iron also upregulates certain genes like CDC2, NDRG1, ALAD, RRM2 in the bulge region of hair follicle, which promote hair re-growth, affected by iron deficiency. 8 Iron supplementation has been suggested prior to and parallel to care. 9 Haemoglobin levels are not representative of true iron status in females with diffuse hair loss.…”
Section: Introductionmentioning
confidence: 99%